The Study of Liquefaction Time Stages due to a Short Duration Shaking - Lindung Zalbuin Mase (Civil Engineering Dimension, 2017)
During the 2006 Yogyakarta earthquake, liquefactions were massively found in Opak River, Yogyakarta, Indonesia. Learning from those events, an experimental study of liquefaction using shaking table was performed, especially to investigate the effect of short shaking duration to liquefaction potential.  Several experimental tests were performed under varied accelerations (0.3g, 0.35g, and 0.4g) and vibration frequencies (1.4 Hz, 1.6 Hz, and 1.8 Hz), with a short shaking duration of 8 seconds. The liquefaction parameter used in this study was the excess pore water pressure ratio. The results revealed that liquefaction occurs in every loading criteria and the short shaking duration applied on each loading influences time stages of liquefaction, i.e. the liquefaction duration, the initial time of liquefaction, and the initial time of pore water pressure dissipation. In addition, the dynamic loads applied in a short duration influenced the maximum excess pore water pressure ratio.